2012
DOI: 10.1007/s00167-012-1885-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage revision of septic knee prosthesis with articulating knee spacers yields better infection eradication rate than one-stage or two-stage revision with static spacers

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
116
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 58 publications
8
116
0
4
Order By: Relevance
“…Our results in terms of survivorship free from infection with the single-stage approach appear comparable to those offered by a systematic review of the results of septic TKA revision, which reported mean eradication rates of 90.6% for two-stage and 89.2% for one-stage surgery [32] as well as with other recent studies on the subject of one-stage exchange [36,39,40]. The higher eradication rate after the two-stage revision, especially in combination with a mobile spacer, was based on numerous publications with shortterm followup and/or a low number of study patients with an eradication rate of up to 100%.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our results in terms of survivorship free from infection with the single-stage approach appear comparable to those offered by a systematic review of the results of septic TKA revision, which reported mean eradication rates of 90.6% for two-stage and 89.2% for one-stage surgery [32] as well as with other recent studies on the subject of one-stage exchange [36,39,40]. The higher eradication rate after the two-stage revision, especially in combination with a mobile spacer, was based on numerous publications with shortterm followup and/or a low number of study patients with an eradication rate of up to 100%.…”
Section: Discussionsupporting
confidence: 80%
“…Standardized diagnostic and therapeutic algorithms for one-stage exchange have been described to make multicenter studies possible with comparable cohorts [13]. Two-stage revision with mobile or static spacers requires at least two surgeries, a longer period of time with limited mobility in the interval, and more possibility for perioperative complications and morbidity [24,28,32,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different treatment strategies can be adopted to counteract orthopaedic infections, depending on overall patient conditions (immune system, joint status and its functionality…) and according to involved pathogens and infection severity [6]. In the vast majority of infected total knee arthroplasty (TKA), one-or two-stage exchange is the preferred option to eradicate infection, with success rate ranging from 80 % to 100 % in different studies [7].…”
Section: Introductionmentioning
confidence: 99%